Controlling desolvation through polymer-assisted grinding. Issue 12 (2nd March 2022) - Terban, Maxwell W.; Madhau, Leillah; Cruz-Cabeza, Aurora J.; Okeyo, Peter O.; Etter, Martin; Schulz, Armin; Rantanen, Jukka; Dinnebier, Robert E.; Billinge, Simon J. L.; Moneghini, Mariarosa; Hasa, Dritan
Abstract : The ability to controllably desolvate a crystal-solvate system in a step-wise fashion through polymer-assisted grinding is demonstrated by varying the type and proportion of polymer agent used. Abstract : We demonstrate the ability to controllably desolvate a crystal-solvate system in a step-wise fashion through polymer-assisted grinding by varying the type and proportion of polymer agent used. A plausible mechanistic explanation is proposed based on a combination of experimental evidence and computational analysis. Specifically, Raman spectroscopy, total scattering pair distribution function analysis and computed reaction energies suggest that the desolvation process is associated with preferred interactions between the solvent molecules and specific polymers. This approach could potentially be extended to any type of material, including heat-sensitive materials, where classical desolvation by thermal processes is not possible, and provides an additional route for formulation processing.